The Role of Selenium in Controlling Reproductive Disorder in Beef Cattle - Ening Wiedosari; Yulvian Sani (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Reproductive failure is regarded as a problem in the breeding of beef cattle as indicated by low calving rate, low conception rate, longer periods of calving interval, and neonatal mortality. Selenium deficiency may lead to non-infectious reproduction disorder in ruminants. The purpose of this review is to evaluate the role of selenium in preventing reproduction failure of beef cattle. In the reproduction process, selenium is required for cellular respiration, cellular oxidation, DNA and RNA replication, the integrity of cells membrane, and releasing free radicals. Selenocysteine (SeCys) is the main component of selenoprotein consisting of glutathione peroxidase (GPX) to inhibit free radicals formation and reduce risks of tissue damage. Glutathione peroxidases (GPXs) involved are: GPX-1 (cytosolic), GPX-2 (gastrointestinal specific), GPX-3 (plasma/extracellular), GPX-4 (phospholipid-hydroperoxides/intracellular) and GPX-5 (spermatozoa mitochondrial capsule). Selenium as an antioxidant is potentially involved in reducing fertility, stillbirth, abortus, and premature in cows based on oxidative stress and selenium deficiency. In male cattle, the role of selenium is to maintain the integrity of cells membrane, spermatozoa fertility, and ejaculation. The selenium deficiency may therefore affect spermatozoa fertility, motility, and fusion to oocytes due to lipid peroxidation. It is then regarded as a factor in reproductive failure mainly in the infertility of cattle. Treatments for reproductive failure due to selenium deficiency could be conducted by supplementing selenium in the mineral mix, periodical dosing of selenium salt, and providing Se-mineral block,  the combination of selenium and vitamin E or selenium supplementation in soils to improve the quality of fodder and feeds.